BAKTERI ENDOFIT PADA PURWOCENG (Pimpinella alpina Kds.) PENGHASIL KUMARIN - , TRI WIDAYAT, Prof. Dra. A. Endang S. Soetarto, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
ndophytic Purwoceng (Pimpinella alpina Kds.) is a an endangered medicinal plant which produces secondary metabolites with efficacy as an aphrodisiac. The plant contains coumarin and interacts with endophytic bacteria. The aims of this research were to determine the location of endophytic bacteria in the purwoceng organs, to isolate the bacteria and to analyze the growth of endophytic bacteria which were grown on coumarin containing medium and the ability of bacteria to produce coumarin. The research was begun with the purwoceng sampling in the Dieng plateau, then proceeded by in planta detection using methylene blue. E bacteria were isolated directly from plant organs containing bacteria. The selection of coumarin-producing endophytic bacteria was based on the ability to survive in ammonium salt sugar (ASS) liquid medium that contained purwoceng herbal infusion. The ability of bacteria to produce coumarin was assayed through experimental cultivation of selected bacterial isolate on the same medium. In every specific time interval the growth was monitored spectrophotometrically and plated on nutrient agar (NA). The obtained data were used to determine the generation time (g) and specific growth rate (Î¼). Coumarin level in the culture was detected by using thin layer chromatography (TLC). Bacterial isolate that produced coumarin was identified by standard methods. Observation under microscope with 400x magnification showed that endophytic bacteria resided and agglomerated in the intercellular space of parenchymal tissue of purwoceng cortex. Nine endophytic bacterial isolates were isolated from the roots and leaves of purwoceng directly. All isolates were able to survive on basal medium containing purwoceng herbal infusion with generation time (g) 2.7 to 5.07 hours and the specific growth rate (Î¼) 0.14 to 0.26/hour. Cultivation of selected isolate showed that BAP5 produced certain compound that was suspected as coumarin derivative with Rf 0.27 on TLC. BAP5 bacteria were able to grow on the medium with coumarin level of 1072 arbitrary units (AU). Coumarin in low level was required by the BAP5 isolate to grow and produce other coumarin derivative. From these results it could be concluded that endophytic bacteria were present in all purwoceng organs. Endophytic bacteria could be grown in the laboratory and produced coumarin derivative.